2011
DOI: 10.3390/ijms12074647
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Interaction with Iron from Yoghurt Using an In Vitro Digestive Model: Comparative Study with Plant Dietary Fibers

Abstract: The objective of this work was to investigate the interaction of chitosan with iron from yoghurt by an in vitro gastrointestinal tract model. Taking into account that chitosan is a polysaccharide included in fiber definition by Codex Alimentarius; chitosan behavior was studied and compared with different plant fiber (wheat, bamboo, apple, psyllium and inulin) behaviors, in the same in vitro conditions. Ferrous sulfate was added to yoghurts with each type of fiber. The gastric environment was simulated with HCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Staffolo et al . () reported that inulin had no iron retention and consequently did not affect the iron bioavailability in yoghurt fortified with 1.3% inulin and 0.8% (w/w) ferrous sulphate. Other studies concluded that inulin did not interfere with iron absorption (Laparra et al .…”
Section: Resultsmentioning
confidence: 99%
“…Staffolo et al . () reported that inulin had no iron retention and consequently did not affect the iron bioavailability in yoghurt fortified with 1.3% inulin and 0.8% (w/w) ferrous sulphate. Other studies concluded that inulin did not interfere with iron absorption (Laparra et al .…”
Section: Resultsmentioning
confidence: 99%
“…In this range of pH, in our work, electrostatic interaction could exist between chitosan-caseinate complexes and iron or calcium. However, when chitosan precipitates, it captures the iron or calcium either by electrostatic forces or by adsorption [138,139].…”
Section: Digestive Chemical Model and Glucose Calcium And Iron Retenmentioning
confidence: 99%
“…In calcium availability studies the digestive mimicking was done without the addition of exogenous calcium because yoghurt is a source of calcium in the diet [138]. To evaluate the interactions between the fibers and iron, 0.8% (w/w) of ferrous sulfate was added to yoghurt samples with each type of fiber [139]. This addition was in accordance with local regulations governing iron supplementation in milk products.…”
Section: Yoghurt Preparationmentioning
confidence: 99%
See 2 more Smart Citations